The Successful Implementation of The Electronic System of Initial Public Offering ("E-IPO") in The Indonesian Capital Market - Rahmanto, Mohamad Ridwan; Suroso, Arif Imam; Bandono, Bayu (Indonesian Journal of Business and Entrepreneurship, 2024)
With a very significant increase in the number of capital market investors, an information system is needed that supports investors to invest more easily and transparently. To facilitate this, the Financial Services Authority ("OJK") in 2020 issued Financial Services Authority Regulation number 41/POJK.04/2020 ("POJK 41"). The pricing, ordering and allotment of securities are carried out through an information system called Electronic Indonesia Public Offering ("E-IPO System"). The E-IPO system aims to provide access to all investors in the Public Offering and booking pricing process so as to increase the participation of all investors. In addition, the use of the E-IPO System is expected to increase transparency and efficiency in the IPO process in order to increase investor confidence in the pre-determined price. As a result of this research, the E-IPO System can be categorized as a good system and has a good net benefit for its users, this is reflected in the condition of information quality, system quality and service quality that affect the use and the satisfaction of E-IPO System users. This will directly or indirectly affect the net profit that will be received by users. Keywords: delone and mclean information system success model, e-ipo, system implementation success, initial public offering, public offering system